ANALYSIS OF CLASS CLEANLINESS ON THE LEARNING CONCENTRATION OF 8th GRADE JUNIOR HIGH SCHOOL STUDENTS - Muhammad Indra Irmansyah; Auli Uzami (Edelweiss : Journal Of Innovation In Educational Research, 2023)
Study This aim For now condition cleanliness class , in class 8 MTS Nurul Faith Selayang And For knowrole as well as student in guard cleanliness class And Also For know influence cleanliness class hapconcentration Study student . Study This characteristic descriptive that is research obtained _ from existsobjects research. As for data collection carried out by writer in making work scientific this , ie with useseveral media such as : Electronic Media (internet), Studies case ( Method collection of the required datawith method interesting sample in sample units certain related _ And students in a manner more in -depth interview to sample . Results study This show that cleanliness really influential to concentrationStudy students , because if something class That dirty so student No will feel comfortable in it . Anywaybenefits that can obtained with guard cleanliness school or class among others , avoided from deploymentdisease And allergy dust , activity Study become more comfortable And focus , environment becomemore beautiful And beautiful , and air become more ok . So come on We guard cleanliness class for morefuture